Tough decisions : cases in medical ethics - Freeman, John Mark (Oxford University Press, 2001)
Life is full of tough decisions that must be made ethically and under the pressures of time. This book places readers in realistic situation where they experience the difficulties of making tough medical decisions. The cases are composites of actual cases the authors have seen or managed. In the role of decision-maker, the reader helps to determine what happens in the case as his or her decision often shapes the course of events and the patient's outcome. This gives a compelling sense of the pressures that bear on clinical decision-making. The authors assume that the reader wants to do the rig.